2018
DOI: 10.1097/mao.0000000000001868
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Sudden Sensorineural Hearing Loss Is Not a Sentinel Event for Acute Myocardial Infarction

Abstract: ISSNHL is not a predictor of an initial AMI in adult patients from the United States. Considerable inconsistencies in associations between cardiovascular risk factors and ISSNHL exist in the literature. Further work is needed to confirm or refute direct associations between cardiovascular disease risk factors and ISSNHL before definitive mechanistic conclusions can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…All studies used administrative datasets. Three studies used the Korean National Health Insurance Service National Sample Cohort (KNH‐NSC) database, 19‐21 three used the Taiwanese National Health Insurance Research Database (NHIRD), 12‐14 and one used the American Truven Health MarketScan Research Database 22 . All studies matched their controls for age and gender.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies used administrative datasets. Three studies used the Korean National Health Insurance Service National Sample Cohort (KNH‐NSC) database, 19‐21 three used the Taiwanese National Health Insurance Research Database (NHIRD), 12‐14 and one used the American Truven Health MarketScan Research Database 22 . All studies matched their controls for age and gender.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, accumulating evidence indicates that cardiovascular risk factors, like smoking and elevated homocysteine levels, may contribute to ISSNHL 15‐18 . Recently, several national database studies have been published investigating if patients with ISSNHL have an increased risk of developing stroke and myocardial infarction (MI) 19‐22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also suggested that patients with ISSNHL had a higher risk of developing future stroke, 12,13 although ISSNHL was not associated with future acute myocardial infarction. 13,14 Quaranta et al reported signs of endothelial dysfunction in ISSNHL and Fisch described the blood pressure dysregulation of the stria vascularis (a process related to age and CVRFs) as a consequence of cochlear atherosclerosis, in which the tunica adventitia loses fibroblasts and becomes thicker, which in turn leads to plasmatic viscosity and platelet aggregation. [15][16][17] As a consequence, vascular pathology is supposed an important etiological factor of ISSNHL.…”
Section: Introductionmentioning
confidence: 99%
“…However, past reviews reported evidence until 2014 and did not report information from some CVRFs (high levels of triglycerides [TG], high‐density lipoprotein cholesterol [HDL‐c], and metabolic syndrome [MetS]) 7 issues that are addressed in the present work. It was also suggested that patients with ISSNHL had a higher risk of developing future stroke, 12,13 although ISSNHL was not associated with future acute myocardial infarction 13,14 …”
Section: Introductionmentioning
confidence: 99%